PENGAJARAN MAYA GURU INOVATIF PENDIDIKAN ISLAM DALAM ERA PANDEMIK COVID-19: VIRTUAL TEACHING OF INNOVATIVE ISLAMIC EDUCATION TEACHERS IN THE COVID-19 PANDEMIC ERA - Mohd Zhaffar, Nursafra; Wan Abdullah, Wan Ali Akbar; Abdul Razak, Khadijah; Hamzah, Mohd Isa (Journal of Islamic Educational Research, 2021)
This study explored the virtual teaching methods practised by the innovative Islamic Education teachers in the Covid-19 pandemic season and its issues. This case study is conducted qualitatively as it is based on a phenomenon. Four participants were selected based on the purposive sampling technique. Four criteria were set, namely; 1) recognized as an innovative teacher, 2) produced teaching innovations, 3) teaching Islamic Education, and 4) approachable and collaborative. Innovative teachers were selected as the participants of the study because they face the crisis calmly and able to find the best solutions. Data were collected using in-depth online interview. The findings showed that five themes were discussed by the participants, namely; 1) preparation, 2) preparation of teaching materials, 3) class schedule, 4) types of teaching, and 5) virtual teaching challenges. Participants have tried their best to provide the best teaching by considering the various challenges occurred during the teaching session.